Radiation‐induced sarcoma of head and neck: Clinical characteristics and molecular signatures - Liao, Yu‐Hao; Hsu, Chia‐Lang; Leu, Chih‐Yu; Lai, Shih‐Fan; Huang, Yen‐Lin; Hsieh, Min‐Shu; Chen, Tseng‐Cheng; Chen, Chun‐Nan; Wang, Cheng‐Ping; Yang, Tsung‐Lin; Tsai, Mong‐Hsun; Lin, Mei‐Chun; et al. (Head & neck, 2023)
Background Radiation‐induced sarcoma of the head and neck (RISHN) is a rare yet devastating potential complication of radiotherapy treatment. We aimed to evaluate the clinicopathological characteristics and molecular signatures of RISHN in patients who underwent radiotherapy for head and neck cancer (HNC) to identify high‐risk patients and enable earlier cancer detection. Methods This study retrospectively evaluated 24 sarcoma patients who received radiotherapy for HNC between 1994 and 2019. Patients were divided into two groups based on RISHN latency period. Patient demographics, initial tumor staging, risk factors, and survival between groups were analyzed, and whole‐exome sequencing (WES) of selected samples was performed. Results The median age at diagnosis of RISHN was 54 years, and the male‐to‐female ratio was 2:1. The latency period ranged from 0.8 to 64.4 years (median 6.5 years), with a median survival of 21.5 months. Primary cancer in the oral cavity, treatment with alkylating agents, alcohol consumption, betel nut chewing, and smoking were identified as risk factors for short (<5 years) latency periods. The majority of RISHN cases occurred in the oral cavity (58.3%). WES analysis showed that tumor necrosis factor and cell cycle checkpoint pathways were differentially involved in both patient groups. Conclusions Although case numbers were small, our cohort represents the largest case series of RISHN from a single institution to date. Clinicians must be aware of factors affecting RISHN development and latency, and risk factor identification may lead to earlier detection and prevention in the future.